Islamophobia and Acts of Extremism Against Muslim Minorities in Sri Lanka Before and During the Covid-19 Pandemic - Mujahidin, Muhammad Saekul (Alfuad: Jurnal Sosial Keagamaan, 2023)
Sri Lanka has witnessed many examples of anti-Muslim sentiment and violence since the end of the civil war, especially in 2014 when an ethnic outbreak affected large numbers of people. Sinhala monks and Buddhists appear to have played an important role in covering it. Long wars and ethnonationalist ideology have resulted in a politico-religious shift related to ÔÇ£Buddhist extremismÔÇØ, which engages in embracing and attacking Muslims. This study uses the "library research" method, whose main data includes: books, journals, articles, and references related to research. Sri Lankan Islamophobia and anti-Muslim sentiment manifests itself in several dimensions such as campaigns warning of Halal products in food, Muslim women's clothing (Burqa), slaughter of livestock in Muslim religious rituals, attacks on mosques and Muslim-owned businesses, and mandatory cremation. for all Sri Lankans regardless of religion at the time of the Corona Virus (Covid-19) outbreak, and the closure of Islamic schools.